A database of ocean primary productivity from the 14C method. Issue 2 (16th November 2020) - Marra, J. F.; Barber, R. T.; Barber, E.; Bidigare, R. R.; Chamberlin, W. S.; Goericke, R.; Hargreaves, B. R.; Hiscock, M.; Iturriaga, R.; Johnson, Z. I.; Kiefer, D. A.; Kinkade, C.; et al.
Abstract: The database on ocean primary productivity comprises over two decades (1985–2008) of data that the authors have participated in collecting, using the assimilation of inorganic 14 C through photosynthesis, in incubations carried out in situ. The dataset is perhaps unique in that it uses, overwhelmingly, consistent methodology while covering a wide geographic range. Ancillary data are included. Using the database, it is hoped that investigators can test for the relationships among the environmental drivers for ocean productivity, the meaning of the 14 C method in terms of phytoplankton physiology and the dynamics in the water column, and as a resource for further development of productivity algorithms using satellite ocean color imagery.